Determinants of Preparing Healthy Breakfast and Snacks for School Children by Mothers - Sakineh Rakhshanderou; Mohtasham Ghaffari; ameneh pooresmaeilidorosteh (Shahid Sadoughi University of Medical Sciences, 2019)
Introduction: An unhealthy breakfast and the consumption of low-value meals among students are associated with adverse health consequences and chronic diseases in adulthood. The main purpose of this study was to identify the determinants of preparing healthy breakfast and snacks for school children by mothers in the city of Islamshahr. Methods: 320 boys and girls were selected by cluster random sampling and their mothers were invited to participate in the study. Data were collected using the researcher-made questionnaire that included demographic characteristics, questions were related to knowledge, attitude, perceived benefits, perceived barriers and behavior. The reliability was assessed through the test-retest method, and in order to assess internal consistency, Chronbach's alpha coefficient was used. Data were analyzed by SPSS 16 software, and Descriptive statistics (Percent & Frequency), Multiple regression and Kendall's tau-b correlation tests were used. Results: Based on the findings of this study, none of the demographic characteristics had a significant correlation with the behavior of the mother's healthy breakfast and meal (p>0.05) and among variables, knowledge (p<0.001, B=0.40) and perceived barriers (p<0.001, B=0.33) were strong and positive predictors of preparing breakfast and healthy snacks by mothers. Knowledge and perceived barriers predict %28 of variance in mothers' behavior in preparing breakfast and healthy snacks (p<0.001, R= 0.527, R2=0.278). Conclusion: It is better to put more emphasis on the strategies to promote the knowledge of mothers and reduce their perceived barriers in designing nutritional interventions aiming to prepare breakfast and healthy snacks for children.